PEASANTS AND FEUDALISM: THE RELEVANCE OF HISTORICAL EVENTS WITH THE LIFE SKILLS CURRICULUM - Siskandar, - (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2010)
The life skills values prevalent among the peasants’ society in the past can be integrated into the content of life skills subject in the historical learning given to students. The expansion of plant products export in the era of Dutch Colonial was significant in the emergence of some changes in the socio-economic life of the peasant and villagers in Java. They were further immersed into the flow of commercialism. The issue in this article is how the response of the farmers to those changes. As an object of observation, this article took the object of study of village areas in Afedeeling Purwerodjo in the beginning of the twentieth century. The methodology used in this article was historical method involving the processes of heuristic, critiques of resources, interpretation, and historiography.The theoretical framework used in this article was dialectics between the assumption that the change of the socio-economic life in the villages into commercialism was a prolong nightmare for the villagers and the assumption that the changed socio-economic life of the villages into commercialism brought new economic opportunities for the villagers. The conclusion was commercialism resulted in rationality and prosperity for the farmers. The peasants would spend their time and energy more efficiently to exploit the new opportunities given. The rational considerations were more determining than the social motivation in terms of decision making. The peasants had the life skills to create beneficial alternative economic resources to support their lives in the middle of a greater flow of foreign plantation commercialism.